Distribution of dissolved and particulate trace metals in Terengganu rever estuary - Teck, William Wong Hoe (IInstitut Oseanografi, 2011)
The distribution of trace metals Cr, Co, Cu, Cd, Pb and Zn between dissolved (total dissolved and CI8 extractable) and suspended particulate matter (SPM) in the Terengganu River estuary was studied in four surveys in 2005 and 2006. The concentration of particulate Cr, Co, Cu, Zn, Cd and Pb were in the range of 2.76|_ig/g - 125.58jug/g, 0.49|.ig/g - 20.64(ig/g, 1.38^ig/g - 57.58ng/g, 0.29^g/g - 183.95^ig/g, 0.06|_ig/g - 1.56|ag/g, and 2.56|ag/g - 78.73|_ig/g, respectively. Concentrations of particulate trace metals declined seawards indicating that the sources of the metals are from the river. In addition, the concentration of particulates was inversely related with salinity especially in the second sampling period, again suggesting river-derived particulate trace metals. The concentrations of particulate trace metals also showed inverse relationship with SPM.